Student’s Perception of Using Google Translate In Writing Task - Fiona, Diah Indah Hayu; Siska; Sevrika, Hevriani (EduCurio: Education Curiosity, 2023)
Students' Perceptions of Using Google Translate in Thesis of English Graduate Program at PGRI University, West Sumatra, Padang 2023. Technologies such as smartphones and computers are well-known tools to help students carry out learning activities. For example, finding study materials needed to translate from English to Indonesian or vice versa. Google Translate is an example of a service that students are interested in translating. The purpose of this study is to describe students' perceptions of the use of Goggle translation in English translation material. In this study, the researchers used qualitative methods. A survey is used to collect data. The subjects of this study were students at SMA Negeri 1 Solok Selatan, where they used Google Translate to translate English material and assist students in writing assignments. The data shows that all students know Google Translate as a translation service from one language to another. Students use glasses to translate, which helps them learn pronunciation and increase vocabulary, and helps them complete writing assignments. This means that students will get to know other functions of Google Translate in the learning process.